Fatal methanol poisoning due to massive windshield screen washer fluid ingestion - case report - Urszula Fałkowska; Agnieszka Radzka; Aleksander Sławiński; Aleksander Ryczkowski; Małgorzata Neścior; Michał Tchórz (Kazimierz Wielki University, 2018)
Methanol is a toxic alcohol that can imitate ethanol in smell and taste. It has many household and industrial applications but can also be present in informally-produced alcoholic beverages. Methanol poisoning feature with high mortality and may be seen due to its intentional or unintentional ingestion. Metanol does not have significant intrinsic activity but its metabolites, especially format lead to severe metabolic acidosis, visual disturbances and neurological deficit. Diagnosis is mainly based upon the typical clinical course, metabolic acidosis with high osmolar gap and detection of methanol in plasma or urine. Recent guidelines recommend therapy using the competitive alcohol dehydrogenase inhibitors - fomepizol or ethanol. In cases of severe poisoning hemodialysis should be considered. We present a case of a 39-year-old male who was considered to Emergency Department due to consumed high amount of windshield washer fluid containing methanol. Intoxicated patient was unstable with respiratory insufficiency and consciousness impairment. Despite of implemented treatment - hemodialysis, ethanol infusion and active respiratory therapy - patient died on seventh day after admission to a hospital. Methanol poisonings feature with high mortality even when the best healthcare is provided. It depends mainly on a dose of ingested alcohol and delay in admission to a hospital.